Computer assisted optimization of cardiac resynchronization therapy - Miri, Raz (Karlsruhe transactions on biomedical engineering / Ed.: Universität Karlsruhe (TH) / Institute of Biomedical Engineering, 2009)
The efficacy of cardiac resynchronization therapy (CRT) through biventricular pacing (BVP) has been demonstrated by numerous studies in patients suffering from congestive heart failure. In order to achieve a guideline for optimal treatment with BVP devices, an automated non-invasive strategy based on an electrophysiological computer model of the heart is presented. The presented research investigates an off-line optimization algorithm based on different electrode positioning and timing delays.